Implementasi Sistem Reminder Jadwal pada eLearning Moodle Berbasis API Menggunakan Framework Flutter - M. Yudha Putra; Dwi Ely Kurniawan (Journal of Applied Computer Science and Technology, 2023)
This research aims to develop a Flutter-based mobile application that provides users with information regarding class schedules and assignments. The application includes a reminder feature that sends notifications about lectures and assignments through WhatsApp and in-app notifications. The development methodology employed is the waterfall model, while testing utilizes black-box testing and Firebase Test Lab. The test results demonstrate the successful development of the application. Additionally, this application facilitates efficient and easy access to class schedules and assignments. It is expected to enhance users' academic performance and be applicable across various educational institutions. Overall, the development of this application offers users the advantage of effectively and efficiently managing study time and completing tasks, thereby contributing to the improvement of educational quality within institutions.